Investigation on L-Histidinium Maleate 1.5-Hydrate Crystals for Nonlinear Frequency Conversion - Helen Merina Albert; C. Alosious Gonsago (Current Approaches in Science and Technology Research Vol. 13, 2021)
L-histidinium maleate 1.5-hydrate (LHM), a new amino acid organic nonlinear optical (NLO) material was synthesized from aqueous solution by slow solvent evaporation method at room temperature. The solubility of the compound was studied in aqueous solution at different temperatures. The structural arrangement the grown crystal was identified using single crystal XRD and powder XRD studies. The chemical composition of the grown crystal was confirmed by Energy dispersive X-ray analysis (EDAX). The percentage of optical transmittance by the grown crystal was identified by UV–visible spectral study. The nonlinear optical property of the grown material was observed by the powder technique of Kurtz and Perry. The surface morphology of the grown crystal was investigated by HR-SEM analysis. The thermal stability of the grown crystal was ascertained by differential thermal analysis and differential scanning calorimetry.